2021
DOI: 10.1038/s41598-021-92006-4
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles produced from Cedecea sp. exhibit antibiofilm activity and remarkable stability

Abstract: With multidrug-resistant bacterial pathogens on the rise, there is a strong research focus on alternative antibacterial treatments that could replace or complement classical antibiotics. Metallic nanoparticles, and in particular silver nanoparticles (AgNPs), have been shown to kill bacterial biofilms effectively, but their chemical synthesis often involves environmentally unfriendly by-products. Recent studies have shown that microbial and plant extracts can be used for the environmentally friendly synthesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 49 publications
(65 reference statements)
2
56
0
Order By: Relevance
“…FT-IR spectrum of bacterial culture supernatant also displayed the identical vibrational stretches at 3256.21, 2931.72, 2877.00, 2021.83, 1997.98, 1592.94, 1452.79, 1395.89 and 1040.80 cm −1 ( Figure 4 B). The results of this study coincided with other reports [ 23 , 27 , 38 ]. FT-IR analysis revealed the binding of carbohydrates, proteins, and phospholipids with synthesized NPs which contributed for the stability of NPs, as well as capping and functionalizing agents.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…FT-IR spectrum of bacterial culture supernatant also displayed the identical vibrational stretches at 3256.21, 2931.72, 2877.00, 2021.83, 1997.98, 1592.94, 1452.79, 1395.89 and 1040.80 cm −1 ( Figure 4 B). The results of this study coincided with other reports [ 23 , 27 , 38 ]. FT-IR analysis revealed the binding of carbohydrates, proteins, and phospholipids with synthesized NPs which contributed for the stability of NPs, as well as capping and functionalizing agents.…”
Section: Resultssupporting
confidence: 93%
“…A similar particle size was formed by Cedecea sp. in the range of 10–40 nm [ 38 ]. Energy dispersive X-Ray (EDX) and elementary mapping was used to investigate the purity and elemental composition of synthesized AgNPs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Singh et al reported a similar particle size (10-40 nm) of AgNPs that was synthesized by Cedecea sp. [43]. The elemental composition and purity of synthesized AgNPs was examined by EDX, as shown in Figure 5.…”
Section: Characterization Of Green Synthesized Agnpsmentioning
confidence: 99%